Emergency call receiving alert through mobile phones using to change the current profile - Rama Lingham N, Siva; Yuvaraj, G; Senthil Murugan, T (International Journal of Engineering and Technology, 2018)
Emergency Call Alert (ECA) Application is developed for inform the urgency as well as seriousness of the call to the receiver. The profile in the mobile facilitates that the user to change the mode they need and this requires manual work load. This Call Manager changes the pro-file automatically to the desired mode designed by the user. It has also been enhanced with filtering mechanism called as Emergency calls filter which allows the calls from the emergency list to be in user preferred mode irrespective of the current mode. This feature is to avoid the missing of calls from the numbers specified in the emergency call list. Now a day most of calls come to us when we are busy, it is an interrupt, which disturbs or sometimes accident may happen. To avoid this either we switch off the mobile or we put the mobile in silent mode. If this is so if any emergency call comes we cannot attend such type of calls. The other disadvantage of this is the calling person does not know when the called person is free. To overcome all these problems we presented paper, Emergency Call Manager which handles all the call when he/she is busy sends an SMS. Software which filters this message and it gives an emergency alarm to called mobile.Â Â